Review of Utilization of Cardiovascular Medicines by Daily Defined Dose in the Czech Republic and Slovak Republic - Szilágyiová, Petra; Slušná, Jana; Babela, Robert (Neuro endocrinology letters, 2017)
To the Editor, Drug utilization is an important field of drug policy and an integral part of public health internationally. This area of research attracts increasing interest but the pioneering work was done 50 years ago when the first drug consumption report from six European countries for the period of 1966-1967 showed great differences in drug utilization between population groups (WHO, 1968). These results gave important stimulus for creation of Anatomical Therapeutic Chemical (ATC) classification and technical unit of measurement called the Defined Daily Dose (DDD) which is specified as "the assumed average maintenance dose per day for a drug used for its main indication in adults" that dealt with the objections against traditional units of measurement in drug utilization studies (WHO, 2016). The ATC/DDD methodology has in the meantime proved its suitability in drug utilization monitoring and research. As mentioned previously, consumption of pharmaceuticals is often used as a basis for comparison between countries. Based on our professional expertise, we decided to analyze the consumption of cardiovascular medicines by DDD in the Czech Republic and Slovak Republic within all ATC groups reported to OECD (OECD, 2016a). According to OECD indicator results, the Slovak Republic showed in 2014 a higher pharmaceutical consumption by DDD in ATC group C (cardiovascular system) compared to the Czech Republic (OECD, 2016a).
Keywords: Drug Utilization; Česká republika; Slovakia; Health Policy; Slovenská republika; lidé; zdravotní politika; spotřeba léčiv; Czech Republic; Humans